Pengaruh Kepemimpinan Manajer Public Relations terhadap Kualitas Manajemen Public Relations dan Korelasinya dengan Efektivitas Sistem Komunikasi Perusahaan - Neni Yulianita (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2002)
The focus of this research was to study the personal skills and leadership functions of the public relations manager which is assumed will bear its influence on the quality of public relations management in order to enhance the effectiveness of the communication system of his organization. The approach used in this research was systems approach in the social-science context which is interlaced with interdicipliner approach from the psychology, communication, sociology,and management perspective. As for the method used was